Assessing the sedative effect of oral vs submucosal meperidine in pediatric dental patients - Lida Toomarian; Katayoun Salem; Ghassem Ansari (Dental Research Journal, 2013)
Background: The goal of this investigation was to compare the behavioral and physiological effects of three sedative drug regimens: oral meperidine (OM), submucosal meperidine (SM) and oral midazolam (M) in healthy pediatric patients. Materials and Methods: This study sample consisted of thirty children aged 24-72 months (mean = 41.1) exhibiting definitely negative behavior. Three sedative regimens including: Oral meperidine/hydroxyzine, oral midazolam/hydroxyzine and submucosal meperidine/oral hydroxyzine were administered randomly during three consecutive appointments with a crossover design. Houpt behavioral scale was employed for evaluating the sedation effect of each regimen by a calibrated independent Pediatric dentist. Physiologic parameters were also recorded including blood oxygen saturation and pulse rate. Data was analyzed using Wilcoxon-signed ranked test, Mc-Nemar, GEE Logistic regression, Friedman, Fisher exact and Cochran tests for significance. Results: Overall success rates were 50%, 46.7% and 26.7% for submucosal meperidine, oral meperidine and oral midazolam, respectively ( P = 0.03). The probability of achieving a success in behavior control was more in 48-72 month olds. Child′s age and drug type were the two main predictors of altered behavior. Evaluating the differences between the effects of three tested regimens on recorded physiological parameters showed no significant differences. Conclusion: All three regimens were proved safe within the limits of the current study. Meperidine sedation in both routes was considered to be more effective. Although there was less sleep and more head/oral resistance in midazolam group, the difference between groups was not significant.